Decision Support System for Selecting Tofu Dregs Suppliers Using the Analytical Hierarchy Process (AHP) Method - Parulian, Dudi; Fazrie, Muhammad; Alima, Ghina (Lembaga Komunitas Informasi Teknologi Aceh (KITA), 2023)
The process of selecting suppliers can be simplified with the aid of a system that offers recommendations for optimal supplier choices. This research aims to develop a decision support system application to assist CV. TJIGOWEK in objectively selecting tofu dregs suppliers while enhancing effectiveness and efficiency in time management. The research methodology employed to facilitate supplier selection is the Analytical Hierarchy Process (AHP). The five fundamental criteria utilized as parameters include quality, quantity, pricing, service, and payment flexibility. The AHP method is employed to determine the weight of each criterion, ultimately generating the optimal alternative ranking. The findings of this study can serve as a valuable reference for making supplier selection decisions aligned with the company's predefined criteria.